2018
DOI: 10.1097/ijg.0000000000000909
|View full text |Cite
|
Sign up to set email alerts
|

Laser Management of Glaucoma in Exfoliation Syndrome

Abstract: Argon laser trabeculoplasty as well as selective laser trabeculoplasty can be used in patients with exfoliation syndrome with similar safety and efficacy. However, treatment effect may abruptly reverse and patients need to be followed regularly to monitor intraocular pressure control. Newer laser treatment modalities including micropulse laser trabeculoplasty, titanium sapphire laser trabeculoplasty and pattern scanning trabeculoplasty show promising results but need to be studied in exfoliation patients. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In a recent review article by Sandhu & Damji (), TCP was proposed as a reasonable option for treatment of refractory PEX glaucoma. It has been suggested that excessive exfoliation material on the zonules can hinder laser uptake in endoscopic cyclophotocoagulation (Francis et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review article by Sandhu & Damji (), TCP was proposed as a reasonable option for treatment of refractory PEX glaucoma. It has been suggested that excessive exfoliation material on the zonules can hinder laser uptake in endoscopic cyclophotocoagulation (Francis et al.…”
Section: Discussionmentioning
confidence: 99%
“…During the years of the recruitment period, COCO procedures accounted for approximately 5% of all glaucoma surgeries in our study center. Overall—in contrast to classic tCPC literature [ 24 , 41 ]—PEX seems to negatively influence efficacy in terms of IOP–SSI after COCO in the same way as PEX may hinder laser uptake in endoscopic CPC [ 42 ]. The finding that PEX is a risk factor for more IOP-SSIs can be explained by the fact that PEX causes chronic progressive congestion of the outflow pathways of the eye by protein material.…”
Section: Discussionmentioning
confidence: 99%